Identification of amino acid residues critical for infection with ecotropic murine leukemia retrovirus. - Yoshimoto, T (1993)
The murine cationic amino acid transporter is also the receptor for murine ecotropic leukemia retrovirus (MuLV-E). Recently, we have cloned a human gene (H13) homologous to the murine ecotropic retroviral receptor (ERR). Although the human homolog is very similar to murine ERR in sequence (87.6% amino acid identity) and structure (14 transmembrane-spanning domains), the human protein fails to function as a receptor for MuLV-E. To identify amino acid residues critical for MuLV-E infection, we took advantage of this species difference and substituted human H13 and murine ERR amino acid residues. Mouse-human chimeric receptor molecules were generated by taking advantage of using common restriction sites. These studies demonstrated that extracellular domains 3 and/or 4 contain the critical amino acid residues. Oligonucleotide-directed mutagenesis was then used to create 13 individual ERR mutants containing one or two amino acids substitutions or insertions within these two extracellular domains. Substitution of as few as one amino acid residue (Tyr) at position 235 in ERR with the corresponding H13 amino acid residue Pro abrogates the ability to function as a receptor for MuLV-E infection. Conversely, substitution of just two amino acid residues at positions 240 and 242 or 242 and 244 in H13 with the corresponding amino acid residues in ERR endows H13 with the ability to function as the receptor. This observation can be utilized to significantly improve the safety of retrovirus-mediated gene therapy in humans.